Toxoplasmosis Encephalitis: A Cross-Sectional Analysis at a U.S. Safety-Net Hospital in the Late cART Era. (16th October 2021) - Lau, Abby; Jain, Mamta Khandelwal; Chow, Jeremy Yan-Shun; Kitchell, Ellen; Lazarte, Susana; Nijhawan, Ank
Despite decreasing incidence of toxoplasmosis encephalitis(TE) among people living with HIV(PLWH) in the late antiretroviral era, U.S. safety-net hospitals still see significant numbers of admissions for TE. Little is known about this population, their healthcare utilization and long-term outcomes. We conducted an 8-year retrospective review of PLWH with TE at a safety-net hospital. Demographics, clinical characteristics, treatments, readmissions, and outcomes were collected. We used chi-squared test to evaluate 6-month all-cause readmission and demographic/clinical characteristics. Of 38 patients identified, 79% and 40% had a new diagnosis of TE and HIV respectively. 59% had 6-month all-cause readmission. Social factors were associated with readmission (uninsured (p = 0.036), Spanish as primary language (p = 0.017), non-adherence (p = 0.030)) and not markers of clinical severity (ICU admission, steroid-use, concomitant infections, therapeutic adverse events). Despite high readmission rates, at follow-up, 60% had a complete response, 30% had a partial response. Improving TE outcomes requires focus on culturally competent, coordinated care.